Promises of Music in Education? - Tervaniemi, Mari; Tao, Sha; Huotilainen, Minna (Frontiers in Education, 2018)
Learning in the school is targeted to master academic skills such as reading, writing, and mathematical skills, as well as to acquire knowledge about different subjects such as history, geography, biology, and so on. However, in the future, successful learning will largely be manifested by the students’ global and transferable skills, such as analytical thinking, problem solving, collaboration, and social skills. Here we introduce the promises of utilizing music to support future learning. We review empirical evidences about the effects of music learning on neurocognitive development in formal and informal settings, in music interventions, and also in community settings. By this review, we wish to stimulate discussion about the roles which music could have in promoting learning in the schools and elsewhere.